3rd International Conference on Movement, Health and Exercise : engineering Olympic success : from theory to practice - Ibrahim, F. (Springer, 2017)
This volume presents the proceedings of the 3rd International Conference on Movement, Health and Exercise 2016 (MoHE2016). The conference was jointly organized by the Biomedical Engineering Department and Sports Centre, University of Malaya. It was held in Malacca, from 28-30 September 2016. MoHE 2016 provided a good opportunity for speakers and participants to actively discuss about recent developments in a wide range of topics in the area of sports and exercise science. In total, 83 presenters and 140 participants took part in this successful conference.
Keywords: Sports sciences -- Congresses.; Sports medicine -- Congresses.; elektronické knihy; electronic books